Comparative antibiogram and clinical efficacy of neomycin in bovine genital infections - RAMPRABHU, R; RAJESWAR, J JOHNSON; PADMANABAN, C; AVADAYAPPAN, T (The Indian Journal of Animal Reproduction, 2023)
Microbial agents isolated from seventy-six cases of bovine genital infections and their antibiotic sensitivity pattern was recorded. E. coli was the most prevalent organism followed by Staphylococcus sp and Streptococcus sp. Maximum per cent of genital isolates were sensitive to neomycin followed by gentamicin, amikacin and ciprofloxacin and were resistant to tetracycline and kanamycin. In the treatment trial, single parentral administration ofneomycin resulted in 84.30% conception rate whereas animals treated with gentamicin resulted in 60% conception only.